2013
DOI: 10.1002/chem.201203113
|View full text |Cite
|
Sign up to set email alerts
|

Azatrioxa[8]circulenes: Planar Anti‐Aromatic Cyclooctatetraenes

Abstract: We describe herein the first synthesis of a new class of anti-aromatic planar cyclooctatetraenes: the azatrioxa[8]circulenes. This was achieved by treating a suitably functionalised 3,6-dihydroxycarbazole with 1,4-benzoquinones or a 1,4-naphthoquinone. We fully characterised the azatrioxa[8]circulenes by using optical, electrochemical and computational techniques as well as by single-crystal X-ray crystallography. The results of a computational study (NICS) suggest that the central planar cyclooctatetraene is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 41 publications
3
56
0
Order By: Relevance
“…21,52,53 sym-Tetraselenatetrathia [8]circulene 10 prepared two years later has a similar planar structure. 22,28 Azaoxa [8]circulenes 23,24 prepared by the group of Pittelkow are the latest synthesized heterocirculenes. Among these compounds are azatrioxa [8]circulene 23 11, its dibenzo derivative comprising two naphthalene moieties 23 and diazadioxacirculene 24 12.…”
Section: Methodsmentioning
confidence: 99%
“…21,52,53 sym-Tetraselenatetrathia [8]circulene 10 prepared two years later has a similar planar structure. 22,28 Azaoxa [8]circulenes 23,24 prepared by the group of Pittelkow are the latest synthesized heterocirculenes. Among these compounds are azatrioxa [8]circulene 23 11, its dibenzo derivative comprising two naphthalene moieties 23 and diazadioxacirculene 24 12.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, the azaoxa[8]circulenes 4 and 5 absorb intensively in the visible region in the range 380-450 nm. Additionally, they demonstrate a relatively high fluorescence quantum yield [31,32]. In order to explain these features we have calculated vibronic structure for the electronic absorption spectra of azaoxa [8]circulenes 4, 5.…”
Section: Azaoxa[8]circulenesmentioning
confidence: 99%
“…In our previous studies [28][29][30][31][32][33][34][35][36][37][38][39][40][41] the structure and electronic absorption spectra of the heteroannelated octatetraenes were described in detail but the vibronic effects have been discussed only qualitatively. As a good example of vibronic effects manifestation the electronic absorption spectrum of the tetraoxa [8]circulene 1 (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DFT studies 13-17 using B3LYP/6-31G(d) were found reliable in predicting experimental vibrational (IR and Raman) and UV-spectra of such π-extended tetraoxa- [8]circulenes. Also, a wide range of hetero- [8]circulenes (such as tetrathio and tetraseleno 20 , octathio 18, 21 , tetraseleno-tetrathio 21 , azatrioxa 22 and diazadioxa [8]circulene 23 properties with corresponding carbon [8]circulenes. These molecular models of [8]BNcirculenes may be considered as the building blocks of crystalline nanoscale materials.…”
Section: Introductionmentioning
confidence: 99%